Tourism Management - Weaver, David B. (David Bruce); Lawton, Laura (Milton, Qld. : John Wiley & Sons, 2010)
Tourism is increasingly widespread & complex, and adaptive management is therefore required to realise its full potential as a sustainable economic, ecological, social & cultural force. 'Tourism Management' provides an introduction to tourism that gives a foundation for further informed engagement with the sector.
Previous ed.: 2006.
Includes bibliographical references and index.
Keywords: Tourism -- Australia -- Marketing; Tourism -- Australia -- Management; Ecotourism -- Australia; Travel and Tourism